2022
DOI: 10.1111/acps.13433
|View full text |Cite
|
Sign up to set email alerts
|

Specific metabolic syndrome components predict cognition and social functioning in people with type 2 diabetes mellitus and severe mental disorders

Abstract: Objective: Obesity and metabolic diseases such as metabolic syndrome (MetS) are more prevalent in people with type 2 diabetes mellitus (T2DM), major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia (SZ). MetS components might be associated with neurocognitive and functional impairments in these individuals. The predictive and discriminatory validity of MetS and its components regarding those outcomes were assessed from prospective and transdiagnostic perspectives.Methods: Metabolic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The course of 0–6 months of HC (5.26%) and SC (7.61%) was very close to the above range. However, some researchers believed that SC had metabolic abnormalities first, and then obesity ( 16 ). When we focused on SC patients with a longer course of disease (over 6 months), we found that the incidence of obesity was higher than the abovementioned data of the healthy population of the national epidemiological survey.…”
Section: Discussionmentioning
confidence: 99%
“…The course of 0–6 months of HC (5.26%) and SC (7.61%) was very close to the above range. However, some researchers believed that SC had metabolic abnormalities first, and then obesity ( 16 ). When we focused on SC patients with a longer course of disease (over 6 months), we found that the incidence of obesity was higher than the abovementioned data of the healthy population of the national epidemiological survey.…”
Section: Discussionmentioning
confidence: 99%
“…Triglycerides were much higher in drug-naïve BD patients and BD patients taking medications than in healthy controls, and triglycerides were found to be associated with cognitive dysfunction and worse cognitive flexibility in BD ( 47 ). Triglycerides were the most accurate factor to identify individuals with greater cognitive impairment from among patients with severe mental disorders ( 48 ). In the general population, triglycerides are an independent risk factor for cardiovascular disease ( 49 ), and could serve as an independent marker for an increased risk of cardiovascular diseases in patients with type 2 diabetes mellitus ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The considerable, and recent, advances in our knowledge of the causes and regulation of the altered-metabolism-based diseases constituting the core of MS have provided consid-erable insight into their nature and the additive/complementary effects within MS [21][22][23][24][25][26]. Despite the considerable number of 'syndromic' traits involved in MS, a careful and systematic analysis of the pathogeny of most of these disorders running together has shown that they share a fairly common number of global mechanisms provoking their surge: inflammation [18,27,28].…”
Section: The Complexity Of Msmentioning
confidence: 99%